Reactions of 5-(4-methoxy-3-methylphenyl)-2(3H)-furanone with some electrophilic and nucleophilic reagents - Soliman, Mohamed Helmy Abd El-hamied; El-Sakka, Sahar Said Ahmed (European Journal of Chemistry, 2017)
5-(4-Methoxy-3-methylphenyl)-2(3H)-furanone was prepared and reacted with some nucleophilic and electrophilic reagents. The condensation of furanone with aromatic aldehydes or phthalic anhydride yielded the corresponding 3-arylidenefuranone derivatives and phthalide, respectively. While the treatment of furanone with amines in refluxing ethanol led to the formation of amides. The reaction of the amides with thionyl chloride afforded the corresponding isothiazolones. The benzimidazole derivative was prepared via the reaction of the 2(3H)-furanone with o-phenylenediamine in boiling ethanol. However, hydrazine hydrate affected ring opening of furanone to give the corresponding acid hydrazide, which underwent in situ cyclization into the corresponding pyridazinone. The base catalyzed ethanolysis of furanone afforded the corresponding ethyl ester.